Pemandu Wisata Inovasi Aplikasi Pariwisata Cerdas Untuk Penyewaan Layanan Pemandu Wisata Di Lembang - Hariman, Irman (INSTITUT DIGITAL EKONOMI LPKIA, 2024)
This research aims to overcome challenges in the Indonesian tourism industry, which in fact faces classic problems such as lack of accessibility of information and references by developing a smart tourism application that supports integration with the smart city vision. With a qualitative approach and Extreme Programming (XP) methodology, research shows that integration of tour guide service preferences with other services is the main key. Therefore, the